Compact Frequency-Agile and Mode-Reconfigurable Antenna for C-Band, Sub-6-GHz-5G, and ISM Applications - Esraa Mousa Ali; Wahaj Abbas Awan; Anees Abbas; Syed Mujahid Abbas; Heba G. Mohamed (Micromachines, 2025)
This article presents the design and evaluation of a compact-sized antenna targeting heterogenous applications working in the C-band, 5G-sub-6GHz, and the ISM band. The antenna offers frequency reconfigurability along with multi-operational modes ranging from wideband to dual-band and tri-band. A compact-sized antenna is designed initially to cover a broad bandwidth that ranges from 4 GHz to 7 GHz. Afterwards, various multiband antennas are formed by loading various stubs. Finally, the wideband antenna along with multi-stub loaded antennas are combined to form a single antenna. Furthermore, PIN diodes are loaded between the main radiator and stubs to activate the stubs on demand, which consequently generates various operational modes. The last stage of the design is optimization, which helps in achieving the desired bandwidths. The optimized antenna works in the wideband mode covering the C-band, Wi-Fi 6E, and the ISM band. Meanwhile, the multiband modes offer the additional coverage of the LTE, LTE 4G, ISM lower band, and GSM band. The various performance parameters are studied and compared with measured results to show the performance stability of the proposed reconfigurable antenna. In addition, an in-depth literature review along with comparison with proposed antenna is performed to show its potential for targeted applications. The utilization of FR4 as a substrate of the antenna along with its compact size of 15 mm × 20 mm while having multiband and multi-mode frequency reconfigurability makes it a strong candidate for present as well as for future smart devices and electronics.